Arbitration in Administrative Affairs: The Enlargement Scope of Ratione Materiae in Portugal - Marta Portocarrero (Central European Public Administration Review)
The purpose of this article is to address the question of arbitrability of administrative conflicts, generally and as characteristic of Portugal. Although the use of arbitration in conflicts where public entities intervene in private relationships is usually allowed, European legislatures commonly consider administrative disputes as a type of controversy excluded from arbitration. It is indeed easy to raise strong arguments against alternative dispute resolution when public administration is implicated. Nevertheless, none of the objections usually raised seems to be unbridgeable. Consequently, the article aims to critically analyse the main arguments against the power of arbitrators to rule on public conflicts. Presently, the Portuguese law allows administrative arbitration in a wide range of areas, from conflicts relating to administrative contracts to conflicts over the legality of administrative authority acts. The assessment of this regime makes it clear that the enlargement of the objective scope of administrative arbitration has to be accompanied by rules, which offer a response to the specific requirements of administrative law and a safeguard of public interest. In this sense, the analysis offers a critical review of the solutions of Portuguese law, which can be also used in comparable legal regimes of other European countries.